2014
DOI: 10.1007/s11999-014-3464-6
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Decompression of Lumbar Stenosis With Transpsoas Interbody Cages and Percutaneous Posterior Instrumentation

Abstract: Background The minimally invasive lateral transpsoas retroperitoneal approach to address lumbar stenosis offers advantages to traditional approaches, including sparing of the AP annulus and longitudinal ligament and less risk to the peritoneal contents and retroperitoneal vascular structures. Few studies have presented longitudinal measures of radiographic indirect decompression and relief of pain and restoration of function using the lateral approach to spine fusion. Question/purposes We determined (1) whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 24 publications
(34 reference statements)
2
67
0
1
Order By: Relevance
“…For example, in cases of degenerative scoliosis, the interbody cage can be inserted from the convex side with a wider safety zone. With the LLIF procedure, an indirect decompression effect on degenerative spondylolisthesis has been reported, which does not require direct surgery on the nerve tissue or on the epidural venous plexus [27][28][29][30] . With PETLIF, an improvement in preoperative radicular symptoms was recognized in all cases due to indirect decompression following the insertion of a cage with a height of 9 or 10 mm and correction of vertebral body spondylolisthesis using PPS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in cases of degenerative scoliosis, the interbody cage can be inserted from the convex side with a wider safety zone. With the LLIF procedure, an indirect decompression effect on degenerative spondylolisthesis has been reported, which does not require direct surgery on the nerve tissue or on the epidural venous plexus [27][28][29][30] . With PETLIF, an improvement in preoperative radicular symptoms was recognized in all cases due to indirect decompression following the insertion of a cage with a height of 9 or 10 mm and correction of vertebral body spondylolisthesis using PPS.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, this technique has already proven to be effective in treating degenerative lumbar spine diseases such as adult deformities and multilevel DDD. [14][15][16][17][18][19][20][21] A study conducted by Castro et al 15 concluded that the LLIF technique, even without posterior supplementation, was effective in treating mild adult scoliosis, providing satisfactory coronal and sagittal correction and clinical improvement of pain and function in spite of the high frequency of subsidence.…”
Section: Resultsmentioning
confidence: 99%
“…13 There are articles in the literature that show the effectiveness of using LLIF to treat degenerative scoliosis and indirect compression of neural elements. [14][15][16][17][18][19][20][21] The objective of this article is to evaluate the survival of level L5-S1 in cases of multilevel disc degeneration treated with 3-or 4-level LLIF with instrumentation to L5, with or without posterior supplementation. To do this we analyzed the rate of reoperation with extension of the arthrodesis to the sacrum or pelvis and also the possible predictive factors associated with the necessity of including L5-S1.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous lateral procedures have been performed worldwide, and variations and technical refinements have been proposed. The procedure has also been extended to a wider range of indications, now including primary and revision surgery for degenerative problems, adult deformity, trauma, and thoracic disc herniation 52,[58][59][60][61][62][63][64][65][66][67] . The most recent advance in lateral approach surgery has received attention for its application to other spinal problems that were not indicated for original LLIF procedures.…”
mentioning
confidence: 99%